Migration and Refugee Policies in Germany New European Limits of Control? - Ette, Andreas (Beiträge zur Bevölkerungswissenschaft, 2017)
International migration is one of the most controversial political topics today which demands innovative approaches of global and regional governance. The book provides a fresh theoretical framework to understand European responses to the international migration of people and explains the dynamics of Germany's migration and refugee policy during the last two decades. Against traditional theories and their inherent focus on the national political sphere, the book highlights supranational and multi-level political processes as increasingly important factors to account for national policy changes. Confronted with the most recent developments of international migration, the study offers students and practitioners the necessary background to participate in today's debates.